Customer Perspective on Food Delivery Service - Noor Zulaikah Mat Zin; Auni Syafiqah Abdul Rahman (CSR International Journal, 2023)
The purpose of this study was to investigate the customer perspective on food delivery service in Kuantan. Therefore, this study applied a quantitative approach and used a cross-sectional survey for data collection. The descriptive analysis study design was implemented to determine the perception of Kuantan residents towards the use of food delivery services. The instrument used in this study was a questionnaire, and data were collected from Kuantan residents (N = 58) around Kuantan. The collected data were then computerised and tabulated using descriptive statistics (frequency and percentage). From the analysis, the results show that most residents agree with the use of food delivery services around Kuantan. It is always on their minds and gives a positive perception, considering that the use of the service facilitates movement and saves time for Kuantan residents. In addition, most respondents agreed that this food delivery service can influence them to buy the products offered. Therefore, food delivery services have a positive effect on the online and business environment in Kuantan because it is one of the most influential and practical means of good marketing skills.